A New Aγ-Globin Chain Variant: Hb F-Sykesville MD [Aγ113(G15)Val → Ile; HBG1: c.340G>A] Detected in a Caucasian Baby. (February 2015) - Patel, Niren; Fixler, Jason; Unguru, Yoram; Kutlar, Abdullah; Kutlar, Ferdane
Abstract The total number of hemoglobin (Hb) variants currently included in the globin gene server database is 1626 (November 12 2014), of which 131 are fetal Hb variants. These variants are observed as two different subunits of fetal Hb, Gγ- and Aγ-globin chains. Of the 131 documented fetal Hb variants, 73 are Gγ- and 58 are Aγ-globin chain variants. Although they are easily detected at birth, as the quantity of γ chains progressively decreases over the first few months of life, they are essentially undetectable after 6 months of age. In this report we discuss the molecular characteristics and diagnostic criteria of a new Aγ chain variant that was detected during newborn screening and named Hb F-Sykesville MD [Aγ113(G15)Val → Ile; HBG1: c.340G>A].